Antimicrobial stewardship program in a Malaysian district hospital: first year experience - Yap, Diana Fui Sing; Yang, Liang Boo; Mukhlis, Roshalina; Pek, Woon Chin; Fan, Kee Hoo (Professional Medical Publications, 2016)
Backgrounds & Objective: Antimicrobial resistance is an alarming public health threat that requires urgent global solution. Implementation of antimicrobial stewardship program (ASP) is an essential practice element for healthcare institutions in gate-keeping judicious antimicrobial use. This study highlighted the development, first year experience, and result of the implementation of ASP utilizing persuasive and restrictive approaches in a Malaysian district hospital.